Adaptive properties and ecological plasticity of promising lines of spring soft wheat in the conditions of the Central Non-Black Earth Regions of Russia - T. A. Barkovskaya; O. V. Gladysheva (Аграрная наука Евро-Северо-Востока, 2024)
In the conditions of the Ryazan region, adaptive properties and ecological plasticity of 8 breeding lines of spring soft wheat (standard Agatha variety) were studied in 2020–2023 according to the "yield" trait using diverse statistical methods. Ecological plasticity (bi), stability (σ2d ), index of environmental conditions (Ij) were determined by S. A. Eberhart, W. A. Russell, variation – by B. A. Dospekhov, stress resistance and genetic flexibility – by A. A. Rossielle, J. Hemblin, index of ecological plasticity – by A. A. Gryaznov, indicator the level of the variety yield stability – according to E. D. Nettevich, homeostaticity (Hom ), breeding value (Sc) – according to V. V. Hangildin, relative stability, stability criterion – according to N. A. Sobolev, multiplicativity (KM) – according to V. A. Dragavtsev. It has been established that the yield level is mostly influenced by the factor "environment" – 51.5 %, the contribution of the factor "genotype" is 11.5 %. The average yield in the experiment was 5.19 t/ha, favorable conditions in 2022 (Ij = 0.50) allowed the yield to be 17.9 % higher than in 2021 (Ij = -0.52). Lines 2-17 (6.24 t/ha) and 21-17 (6.05 t/ha) had high yields, their genetic flexibility index was 5.58 and 5.41 t/ha, respectively. Lines 1-17, 465-17 and 531-17 had the highest resistance to stress (-0.63, -1.00), they are characterized by high yield stability (σ2d = 0.27–0.65) and the least decrease in it under adverse conditions. Strong responsiveness to changes in environmental conditions was noted for lines 290-17, 2-17 and 21-17: bi – 1.25–1.29, KM – 2.22–2.27. According to the degree of homeostaticity, line 1-17 was distinguished (Sc – 4.63, PUSS – 212, Hom – 18.3), these indicators exceeded the average values by 10.2 %, 81.0 abs. %, 98.9 %, respectively. According to the results of the integrated assessment by the ranking method, breeding lines 1-17; 465-17 and 21-17 showed varying degrees of adaptability, environmental stability, homeostaticity and had a high rating. The lowest rating in terms of the sum of the ranks of adaptability and plasticity parameters was obtained by the standard Agate variety.